A case of paraplegia arising from mycotic aortic aneurysm - Hamzah Saleem; Yuen-Joyce Liu; Mohammad Sarhan; Eun Kyu Dong (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Mycotic aortic aneurysms are a rare entity. In this report, we consider a patient with mycotic thoracic aortic aneurysm and paraplegia without any evidence of overt infective spondylitis, vertebral osteomyelitis, or spinal abscess. Clinical presentation, treatment, and complications unique to our case are considered.